Proyecto de inversión para la implementación de un spa con técnicas orientales en la ciudad de Guayaquil - Naranjo Méndez, Belén Estefanía (2010)
The investment project involves the implementation of an oriental spa aesthetic and therapeutic with techniques and product 100% natural. The project involves the recruitment of skilled foreign labor, from Thailand and China, recognized worldwide for the quality of their massage techniques, leasing of a commercial local in the sector of the Guayaquil city called Urdesa, and the hiring of 10 people more to work in the business. This business idea arises due to the demand for such services has grown considerably in recent years and there aren’t also significant barriers to entry or exit, moreover the market for spas is new in our country. To finance this project, we hope count with own resources of the partners and a loan to a bank, in adittion this project count with positives cash projections since the firts year of operations and with great potencial for expansion.